Pervasive post-transcriptional control of genes involved in amino acid metabolism by the Hfq-dependent GcvB small RNA. - HINTON, JAY (My University, 2011)
GcvB is one of the most highly conserved Hfq-associated small RNAs in Gram-negative bacteria and was previously reported to repress several ABC transporters for amino acids. To determine the full extent of GcvB-mediated regulation in Salmonella, we combined a genome-wide experimental approach with biocomputational target prediction. Comparative pulse expression of wild-type versus mutant sRNA variants revealed that GcvB governs a large post-transcriptional regulon, impacting ~1% of all Salmonella genes via its conserved G/U-rich domain R1. Complementary predictions of C/A-rich binding sites in mRNAs and gfp reporter fusion experiments increased the number of validated GcvB targets to more than twenty, and doubled the number of regulated amino acid transporters. Unlike the previously described targeting via the single R1 domain, GcvB represses the glycine transporter CycA by exceptionally redundant base-pairing. This novel ability of GcvB is focused upon the one target that could feedback-regulate the glycine-responsive synthesis of GcvB. Several newly discovered mRNA targets involved in amino acid metabolism, including global regulator Lrp, question the previous assumption that GcvB simply acts to limit unnecessary amino acid uptake. Rather, GcvB rewires primary transcriptional control circuits and seems to act as a distinct regulatory node in amino acid metabolism.
PUBLISHED
Keywords: Immunology; Biochemistry; small RNA; Immunology, Inflammation & Infection